Link and Match Program Implementation: A Case Study at Vocational High School 1 Batam - Albert Efendi Pohan; Fauziah Nasution; Santy Mery (Edcomtech: Jurnal Kajian Teknologi Pendidikan, 2023)
The link and match program is implemented to increase the absorption of vocational school graduates into the world of industry and work. This research describes the implementation management of the link and match program at SMK Negeri Satu Batam. A qualitative research method with a case study approach was applied to achieve the research objectives. Data collection techniques were carried out using observation, documentation,, and in-depth interviews. The sources of information for this research were the principal, four deputy principals, three work unit heads, five alumni, and three experts from industry. Validation of research data is triangulation. Data analysis techniques consist of data collection, presentation, condensation, and concluding. Research findings show: (a) Planning was designed by reviewing government regulations regarding the implementation of the link and match program; (b) The school principal determines organization by forming a professional work team; (c) Implementation is carried out by collaborating with industry, optimizing particular job markets (BKK), and providing industrial classes; (d) The supervision of the school principal carries out control and; (e) The integration function consists of teacher apprenticeship programs, competency test certificates, standard work procedures according to industry standards, benchmarking programs, and visits to secondary schools abroad. Furthermore, the integration function as a novelty in this research is a factor in the success of implementing the link and match program which other vocational schools in Indonesia can adopt.